STUDENTS PERCEPTIONS OF COMPUTER FACULTY AND HEALTH FACULTY ON ACCOUNTING COURSE - Meikhati, Ety; Okfitasari, Antin (International Journal of Psychosocial Rehabilitation, 2020)
Abstract: The development of accounting will not be separated from the development of information technology. Learning accounting courses for students of computer faculty and health faculty becomes essential, considering the programs are preparing informatics experts who are able to create an information system to help business problems within the company or hospital. The purpose of this study is to compare the perception of student computer faculty and health faculty on the accounting course. The populations are the students of Management Informatics of Indonusa Polytechnics and the students of the health faculty of Duta Bangsa Surakarta University who passed the accounting course. The sample was chosen by purposive sampling. Data were collected by survey method through questionnaire distribution. Data analysis was to obtain answers to students' perceptions of accounting by using quantitative analysis in the form of descriptive statistics. The results showed that the perceptions of both Information Management and Medical Records students are the same in terms of benefits of studying accounting, relevance and urgency of information management/ medical records, ease in studying accounting, but different perceptions on the factors affecting the success of studying accounting.